Attitudes of Dilated Cardiomyopathy Patients and Investigators Toward Genomic Study Enrollment, Consent Process, and Return of Genetic Results. Issue 2 (27th October 2020) - Blazek, Alisa D.; Kinnamon, Daniel D.; Jordan, Elizabeth; Ni, Hanyu; Hershberger, Ray E.
Abstract : Precision medicine genetics study design requires large, diverse cohorts and thoughtful use of electronic technologies. Involving patients in research design may increase enrollment and engagement, thereby enabling a means to relevant patient outcomes in clinical practice. Few data, however, illustrate attitudes of patients with dilated cardiomyopathy (DCM) and their family members toward genetic study design. This study assessed attitudes of 16 enrolled patients and their family members (P/FM), and 18 investigators or researchers (I/R) of the ongoing DCM Precision Medicine Study during a conjoint patient and investigator meeting using structured, self‐administered surveys examining direct‐to‐participant enrollment and web‐based consent, return of genetic results, and other aspects of genetic study design. Survey respondents were half women and largely identified as white. Web‐based consent was supported by 93% of P/FM and 88% of I/R. Most respondents believed that return of genetic results would motivate study enrollment, but also indicated a desire to opt out. Ideal study design preferences included a 1‐hour visit per year, along with the ability to complete study aspects by telephone or web and possibility of prophylactic medication. This study supports partnership of patients and clinical researchers to inform research priorities and study design to attain the promise of precision medicine for DCM.